Challenges for the Newborn Following Influenza Virus Infection and Prospects for an Effective Vaccine - Alexander-Miller, Martha A. (Frontiers in Immunology, 2020)
Newborns are at significantly increased risk of severe disease following infection with influenza virus. This is the collective result of their naïve status, altered immune responsiveness, and the lack of a vaccine that is effective in these individuals. Numerous studies have revealed impairments in both the innate and adaptive arms of the immune system of newborns. The consequence of these alterations is a quantitative and qualitative decrease in both antibody and T cell responses. This review summarizes the hurdles newborns experience in mounting an effective response that can clear influenza virus and limit disease following infection. In addition, the challenges, as well as the opportunities, for developing vaccines that can elicit protective responses in these at risk individuals are discussed.